Public Consortia for the Treatment of Waste: Analysis from the Principle of Systemic Vision (Global Journal of Human-Social Science, 2020)
In Brazil the National Policy on Solid Waste Law No 12 305 brought new guidelines for waste management and incorporated into its text principles that were previously only in the doctrine especially the one that deals with the systemic view which considers the variables environmental social economic cultural technological and public health This article analyzes the advantages and challenges of intermunicipal consortium for the integrated management of domestic solid waste in the light of the principle of systemic vision since it presents itself as a possibility of facing the difficulties that present themselves This is a bibliographical study It is concluded that public consortia can be a viable and advantageous alternative in the search for joining efforts to solve common problems to meet PNRS requirements since they have advantages in all dimensions related to the principle of systemic vision
Keywords: domestic solid waste; integrated management; intermunicipal public consortium